Impact of Quantitative Evaluation Methods on the Quality of Scientific Research Conducted by University Teachers - Vasilijević, Danijela N.; Sudzilovski, Danijela M.; Marinković, Snežana S. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
The theoretical part of this paper analyzes the issue of professional development of university teachers in the context of lifelong learning, points out the character of currently used methods of evaluation of their scientific research, as well as the importance and effects of legislation that deals with quantitative methods for the evaluation of scientific research conducted by university teachers and associates.The methodological framework of the research is based on the research goal focused on examining opinions of teachers and associates at teacher training faculties about the contribution of quantitative evaluation methods of scientific research conducted to the quality of professional development and scientific research of teachers and associates at teacher training faculties with respect to a) belonging to the university where they are employed, b) experience, c) gained scientific degree, d) the number of papers published on the SCI list.The overall objective of the research was realized through two research objectives: 1) to examine how teachers at teacher training faculties perceive the impact of quantitative methods for the evaluation of scientific research on the quality of their own scientific research; 2) to establish how teachers see the correlation between the quality of scientific research and normative acts of the university related to election and appointment to teaching positions; 3) to determine whether and to what extent existing quantitative evaluation methods affect the autonomy of researchers in terms of the choice of their research content and time dynamics. By implementing the descriptive method, Likert attitude scale, we examined and analyzed the attitudes of 97 teachers and associates at teacher training faculties in Užice, Belgrade, Vranje and Jagodina. Results show that, in the opinion of teachers and associates at teacher training faculties, quantitative evaluation methods do contribute to the quality of teaching and professional development of both teachers and associates, but not to a sufficient extent.